2015
DOI: 10.1177/1759091415578713
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 EP2 Receptor Deletion Attenuates Intracerebral Hemorrhage-Induced Brain Injury and Improves Functional Recovery

Abstract: Intracerebral hemorrhage (ICH) is a devastating type of stroke characterized by bleeding into the brain parenchyma and secondary brain injury resulting from strong neuroinflammatory responses to blood components. Production of prostaglandin E2 (PGE2) is significantly upregulated following ICH and contributes to this inflammatory response in part through its E prostanoid receptor subtype 2 (EP2). Signaling through the EP2 receptor has been shown to affect outcomes of many acute and chronic neurological disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 48 publications
(82 reference statements)
1
42
1
Order By: Relevance
“…Ablation of the EP2 receptor reduces hemorrhage‐induced brain injury‐associated BBB breakdown (Leclerc et al . ). In these mice, there is also a significant reduction in microglial and astrocyte activation associated with the hemorrhage‐induced brain injury, suggesting an important interplay between the EP2‐PGE 2 axis.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Ablation of the EP2 receptor reduces hemorrhage‐induced brain injury‐associated BBB breakdown (Leclerc et al . ). In these mice, there is also a significant reduction in microglial and astrocyte activation associated with the hemorrhage‐induced brain injury, suggesting an important interplay between the EP2‐PGE 2 axis.…”
mentioning
confidence: 97%
“…; Leclerc et al . ). This increases PGE 2 movement from the vascular space into the brain, where it can stimulate an anti‐inflammatory response in microglia (Zhang and Rivest ; Blais et al .…”
mentioning
confidence: 97%
“…Interestingly, contrary to their in vitro data and our in vivo data, the same group later reported that EP2 deletion decreases ICH-induced brain damage and improves functional recovery in young adult mice. 42 Such contradictory in vivo data may be attributable to the differences in the age of the animals studied (middle-aged mice versus young adult mice) and the lesion size of the wild-type control mice (4.3 versus 17.8 mm 3 ). This discrepancy supports a previous hypothesis that the effect of ICH on activation of certain pathways depends on hematoma size.…”
mentioning
confidence: 99%
“…Consequently, inflammation-related inhibition of the PGTand OAT3-mediated PGD 2 transport regulates the PGD 2 levels in the CSF, hence, this should be considered when developing new therapeutic targets for insomnia . Nevertheless, care should be taken as PGE 2 is implicated in neuroinflammation (Leclerc et al, 2015) and PGE 2 clearance occurs via the same transporters as PGD 2 (e.g. OAT3) .…”
Section: Sleep and Sleep Disordersmentioning
confidence: 99%